High‐strength concrete based on ternary binder with high pozzolan content. (1st March 2018) - Vejmelková, Eva; Koňáková, Dana; Čáchová, Monika; Záleská, Martina; Svora, Petr; Keppert, Martin; Rovnaníková, Pavla; Černý, Robert
Abstract : Several high‐strength concrete mixes containing ternary binders composed of Portland cement, silica fume, and waste brick powder are designed. Taking into account the functional properties of hardened mixes, together with their supposed environmental qualities and economic benefits, the practical limits of pozzolan content in the binder are analyzed. Based on a wide set of material characterization experiments including mercury intrusion porosimetry, scanning electron microscopy, and X‐ray diffraction analysis, complemented with a series of measurements of basic physical properties, mechanical parameters, and water and water vapor transport properties, the binder consisting of 57% Portland cement, 18.5% silica fume, and 24.5% brick powder is identified as the optimum in the studied system. The excellent functional properties of the mix with such a high pozzolan content are achieved due to the synergetic effects of the combination of silica fume and waste brick powder on concrete properties. The fineness of brick particles, together with the dual character of the applied brick powder acting as active pozzolan and microfiller at the same time, is found to magnify the ability of silica fume to fill the intergranular space through the improvement of the granulometry curve.